Anthelmintic resistance in grazing beef cattle in central and northeastern areas of Argentina — An update - Cristel, Silvina (2017)
The presence of anthelmintic resistance in Argentina has experienced a marked increase in cattle, with numerous reports showing levels of resistance of different parasite genera to different chemical groups. The aim of this study is to update comprehensively the situation of anthelmintic resistance to the different chemical groups in the most important areas of cattle production in Argentina. The study involved the determination of anthelmintic resistance in 62 cattle farms in 7 provinces using the faecal egg count reductions test. The results showed a marked increase of anthelmintic resistance compared to previous reports; the main resistant genera were Cooperia and Haemonchus to ivermectin, Ostertagia and Cooperia to ricobendazole, and Haemonchus to fenbendazole. There was also a distinct difference in clinical efficacies between subcutaneous ricobendazole and oral fenbendazole in favour of the latter, probably attributed to the administration route. Levamisole has showed high efficacy and broad antiparasitic spectrum. Anthelmintic resistance is widely and firmly established in grazing cattle production systems in the country; the diagnosis of resistance must be done in every particular farm in order to design a sustainable parasite control based on anthelmintics use.